Effect of Self Efficacy Training on Diet and Blood Glucose Compliance in Diabetes Type 2 Mellitus Patients - Hariyono Hariyono (Journal of Global Pharma Technology, 2020)
Background: Self-efficacy training is an effective way for people with diabetes mellitus to get improved blood glucose compliance and control. The purpose of this study was to analyze the effect of self-efficacy training on diet compliance and blood glucose. Methods: This study used a quasi-experimental pre-post-test with a control group. The population of this study was all Diabetes Mellitus patients in the Public Health Center area with 17 sample respondents for each group. The sampling technique was purposive sampling. The variables of this study were: self-efficacy training, diet compliance, and blood glucose. The way to collect data was by using questionnaires and laboratory examinations. Result: The results showed that self efficacy training did not affect the adherence of diabetic patients in either the intervention group or the control group with the Wilcoxon test results showing the intervention group (p = 0.863 (p <0.05)), the control group (p = 0.677 (p < 0.05)) and the Mann-Whitney test (p = 0.909 (p> 0.05)). The second result showed that self-efficacy training had an effect on blood glucose in patients with Diabetes Mellitus in the intervention group but did not affect the control group, according to the Wilcoxon test results showed for the intervention group (p = 0.003 (p <0.05), the control group (p = 0.163 (p> 0.05) and the Mann-Whitney test (p = 0.080 (p> 0.05). Discussion: self-efficacy training can improve blood glucose control quite well, but still requires integration with other components related to the pillars of Diabetes Mellitus management. Self-efficacy training is not significant enough to improve the adherence of diabetic patients but with increased knowledge and behavior, it is hoped that they will be able to increase their motivation to support increased self-care abilities, change behavior and carry out activities to maintain glycemic control.Keyword: Self Efficacy Training, Diet Compliance, Blood Glucose, Glycemic Control, Diabetes Mellitus.